CONCEPTUAL FRAMEWORK ON E-LEARNING READINESS IN SULTANATE OF OMAN - Salem Hamad Saeed Al Hasani; Nor Azilah Husin (Journal of Islamic, Social, Economics and Development, 2021)
Regular education in Oman faces many problems. This study aims to review the impact of environment, finance, and knowledge on the speed of use e-learning at Sultanate of Oman, as the speed of the Environment and Knowledge leads to the development of e-learning performance in the Sultanate of Oman. The Secondary Research Approach method was used by reviewing 29 articles from various sources such as websites, books, journals, and scholarly research, from January 2021 to July 2021. The results indicated that the environment and knowledge have a significant impact on the performance of e-learning readiness. The inclusion of e-learning readiness revealed the conceptual model for the effect of complementary mediation on the relationship between knowledge and e-learning readiness and the performance of the technology. This study demonstrates the importance of e-learning readiness and meeting user expectations. The results contribute significantly to both theory and practice by promoting the use of e-learning readiness.